2006
DOI: 10.1007/s10495-006-4689-y
|View full text |Cite
|
Sign up to set email alerts
|

JNK and AP-1 mediate apoptosis induced by bortezomib in HepG2 cells via FasL/caspase-8 and mitochondria-dependent pathways

Abstract: The proteasome inhibitor bortezomib is an efficacious apoptotic agent in many tumor cells. This paper shows that bortezomib induced apoptosis in human hepatoma HepG2 cells associated with many modifications in the expression of survival or death factors. Although bortezomib increased the level of the protective factors HSP70 and HSP27, the effects of the drug that favour cell death were predominant. These events include accumulation of c-Jun, phospho-c-Jun and p53; increase in FasL level with activation of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 62 publications
8
72
0
Order By: Relevance
“…Some studies have shown that JNK regulates DR5 expression (6,41,42). Although PS-341 indeed induced JNK activation in our cell lines as shown previously (20,21), we found that the JNK inhibitor SP600125 only weakly attenuated PS-341-induced DR5 induction, 1 suggesting that other mechanism(s) beyond JNK may be involved in PS-341-induced DR5 expression in human NSCLC cells. Because PS-341 induces endoplasmic reticulum stress, including up-regulation of CHOP/ GADD153 (43,44), a transcriptional factor known to regulate DR5 expression (27,45), it remains to be determined whether PS-341 induces a CHOP-dependent up-regulation of DR5.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some studies have shown that JNK regulates DR5 expression (6,41,42). Although PS-341 indeed induced JNK activation in our cell lines as shown previously (20,21), we found that the JNK inhibitor SP600125 only weakly attenuated PS-341-induced DR5 induction, 1 suggesting that other mechanism(s) beyond JNK may be involved in PS-341-induced DR5 expression in human NSCLC cells. Because PS-341 induces endoplasmic reticulum stress, including up-regulation of CHOP/ GADD153 (43,44), a transcriptional factor known to regulate DR5 expression (27,45), it remains to be determined whether PS-341 induces a CHOP-dependent up-regulation of DR5.…”
Section: Discussionsupporting
confidence: 79%
“…Many preclinical studies documented that PS-341 alone or in combination with other cancer therapeutic agents, including TRAIL, induces apoptosis in a variety of human cancer cells in vitro, including both hematologic and solid tumor malignancies, and inhibits the growth of tumor xenografts in vivo (16,17). However, the molecular mechanisms underlying PS-341-induced apoptosis and enhancement of apoptosis when combined with other agents, including TRAIL, particularly in human lung cancer cells, remain largely uncharacterized, although it seems to be associated with nuclear factor-nB inhibition (14,18,19), c-Jun NH 2 -terminal kinase (JNK) activation (19)(20)(21), or Bik and Bim accumulation (22,23) shown in certain types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…B, quantification of phospho-JNK1/2 expression in MM xenograft tumors. The relative intensity of phospho-JNK1/2 expression was quantified using ImageJ software; *, P < 0.05. mediating bortezomib-induced apoptosis (23,(35)(36)(37)(38). Because disruption of polyamine homeostasis augments JNK activity (39-41), we hypothesized that JNK would also mediate the combination effects of bortezomib and CGC-11093.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the role of JNK as a potential regulator of cell death induced by the CGC-11093/bortezomib combination as we and others have shown that JNK activation contributes to bortezomib-induced apoptosis (23,(35)(36)(37)(38). Furthermore, polyamines have been reported to control JNK activity (39)(40)(41), and thus, we hypothesized that CGC-11093 would augment JNK activity stimulated by bortezomib.…”
Section: Discussionmentioning
confidence: 99%
“…The major stress-inducible isoform of the hsp70 family, hsp72, is expressed in human tumors, correlates with poor prognosis, and contributes to resistance to cancer therapy (29)(30)(31). Proteasome inhibitors seem to up-regulate hsp synthesis by increasing the amount of misfolded proteins as shown in breast tumor, hepatoma HepG 2 , myeloma, and B-lymphoma cells (32)(33)(34)(35)(36). Similar to these reports, in this study, hsp72 up-regulation occurred very early after the exposure of the two colorectal cancer cell lines, Caco-2 and HRT-18, to bortezomib.…”
Section: Discussionmentioning
confidence: 99%